2013
DOI: 10.1175/mwr-d-12-00168.1
|View full text |Cite
|
Sign up to set email alerts
|

Radar Data Assimilation with WRF 4D-Var. Part I: System Development and Preliminary Testing

Abstract: The major goal of this two-part study is to assimilate radar data into the high-resolution Advanced Research Weather Research and Forecasting Model (ARW-WRF) for the improvement of short-term quantitative precipitation forecasting (QPF) using a four-dimensional variational data assimilation (4D-Var) technique. In Part I the development of a radar data assimilation scheme within the WRF 4D-Var system (WRF 4D-Var) and the preliminary testing of the scheme are described. In Part II the performance of the enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 67 publications
1
109
0
1
Order By: Relevance
“…Because of the growing interest in the WRFDA system and associated community-based developments, the WRFDA system has been equipped with extensive capability to assimilate various types of observations. The WRFDA system has DA options such as three-dimensional variational data assimilation (3D-Var), 4D-Var, and hybrid variational-ensemble DA that permit assimilating a wide range of observations including in situ measurements, Doppler radar reflectivity, precipitation, and radiances (Barker et al 2012;Wang et al 2013). For example, the 3D-Var assimilation of conventional ground-based data and radiance observations has been used for improving precipitation forecasts at various spatial resolutions (Ha et al 2011;Ha and Lee 2012;Hsiao et al 2012;Liu et al 2012;Routray et al 2010;Schwartz et al 2012;Xu and Powell 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the growing interest in the WRFDA system and associated community-based developments, the WRFDA system has been equipped with extensive capability to assimilate various types of observations. The WRFDA system has DA options such as three-dimensional variational data assimilation (3D-Var), 4D-Var, and hybrid variational-ensemble DA that permit assimilating a wide range of observations including in situ measurements, Doppler radar reflectivity, precipitation, and radiances (Barker et al 2012;Wang et al 2013). For example, the 3D-Var assimilation of conventional ground-based data and radiance observations has been used for improving precipitation forecasts at various spatial resolutions (Ha et al 2011;Ha and Lee 2012;Hsiao et al 2012;Liu et al 2012;Routray et al 2010;Schwartz et al 2012;Xu and Powell 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, initial conditions are given only for cloud and rain waters but they are soon converted to ice materials with the nonlinear model (JMANHM). As shown in Kawabata et al (2011) and Wang et al (2013), warm rain initial condition seems acceptable for most deep convection predictions, and Wang et al (2012) indicated that a simplified warm rain scheme can be used for high-resolution 4D-Var in a short time assimilation window.…”
Section: Summary and Discussionmentioning
confidence: 91%
“…WRFDA is developed and maintained at the National Center for Atmospheric Research (NCAR) and has been widely used both in research communities and operational centers (Barker et al, 2012;Huang et al, 2009;Wang et al, 2013b). A brief description of WRFDA will be presented in the next section.…”
Section: Implementation In Wrfdamentioning
confidence: 99%